Public Administration and the Evolution of Administrative Law: From Institutional ‎Logic to Organizational Logic - Erraou, Mohammed (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study explores the transformation of public administration and administrative law from an institutional logic to an organizational logic in response to globalization and the diffusion of liberal economic values. It aims to analyze how this shift, driven by New Public Management (NPM), has affected traditional administrative law frameworks, particularly in countries with specific administrative legal systems and jurisdictions. Methods: A conceptual and comparative approach was employed to examine the evolving relationship between administrative law and public administration. Relevant literature and legal frameworks were reviewed to assess how managerial principles have influenced administrative reforms and reshaped the roles of legality, public-private boundaries, and judicial oversight. Results: The findings reveal that the traditional application of administrative law—rooted in the principle of legality—has increasingly been adapted or replaced by managerial models emphasizing flexibility, efficiency, and profitability. Many countries have restructured their public sectors according to NPM principles, resulting in significant changes to public management practices and judicial control mechanisms within administrative jurisdictions. Conclusions: Administrative law now faces the challenge of reconciling managerial rationality with foundational legal principles. The shift from institutional to organizational logic has significant implications for governance, especially in legal systems that maintain distinct administrative courts and laws. Effective integration of these managerial models requires a careful balance to preserve public interest and legal accountability.